Empowering Post Partum Mothers Through Feeding Egg Whites to Acceleration of Perineum Wounds: Pemberdayaan Ibu Nifas Melalui Pemberian Putih Telur Untuk Percepatan Luka Perineum (JURNAL UNEJ, 2024)
Postpartum is the process of healing or restoring the reproductive organs after pregnancy and childbirth to return to their pre-pregnancy state. One of the recovery processes is the recovery of perineal wounds resulting from the birth process. This community service aims to improve the health of postpartum mothers and their families as well as empowering the abilities of postpartum mothers in the socio-economic field at the Ngrandu District Health Center. Ponorogo. The method used is to provide counseling, assistance and guidance to postpartum mothers for 6 months in 3 activities. The target of community service is 10 postpartum mothers. As a result of community service, 100% of postpartum mothers do not experience infections in perineal wounds, 60% of postpartum mothers have good knowledge about high protein diets and the remaining 40% have sufficient knowledge. It is hoped that the nutritional needs of postpartum mothers can be met by consuming foods high in protein to speed up wound healing.